Trinidad and Tobago : 2010 Article IV Consultation-Staff Report, Supplement, Staff Statement, Public Information Notice on the Executive Board Discussion, and Statement by the Executive Director for Trinidad and Tobago. (IMF Staff Country Reports; Country Report, 2011)
The economic slowdown as a result of the global crisis has been severe, and the recovery has not yet taken hold. Despite ample buffers, including large fiscal space and strong international reserves, the policy response to the crisis has been constrained. Inflation has resurfaced as a concern after falling to a historical low in 2009, but the data are misleading. The monetary policy stance has been generally supportive but ineffective in the context of large excess liquidity. Medium-term growth prospects depend on the energy sector outlook.